2021
DOI: 10.1101/2021.03.17.434752
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early-Emerging and Highly-Heritable Sensitivity to Human Communication in Dogs

Abstract: Dogs exhibit similarities to humans in their sensitivity to cooperative-communicative cues, but the extent to which they are biologically prepared for communication with humans is heavily debated. To investigate the developmental and genetic origins of these traits, we tested 375 eight-week-old dog puppies on a battery of social-cognitive measures. We hypothesized that if dogs' social skills for cooperating with humans are biologically prepared, then these skills should emerge robustly in early development, no… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Although there remains much to be learned about the genetic bases of complex traits in dogs, it is already clear that many behavioral traits critical to working dog success are strongly influenced by genetic factors (114,(133)(134)(135)(136). As described below (see section 1.2.2), this knowledge has important applications in the context of breeding dogs for working roles.…”
Section: Genetic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there remains much to be learned about the genetic bases of complex traits in dogs, it is already clear that many behavioral traits critical to working dog success are strongly influenced by genetic factors (114,(133)(134)(135)(136). As described below (see section 1.2.2), this knowledge has important applications in the context of breeding dogs for working roles.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Breeding for behavioral traits has proven to be more difficult, in part due to the challenges of large-scale adoption of standardized phenotyping procedures. Currently the genetic contribution to many behavioral traits remains poorly understood, but heritability studies are becoming increasingly common (71,133,134,136,(209)(210)(211)(212)(213)(214). To our knowledge, most working dog organizations that currently incorporate behavioral measures in EBVs rely on organization-specific phenotyping procedures which are often tailored to specific working roles.…”
Section: Behavior (Temperament and Cognition)mentioning
confidence: 99%
“…Over the past few decades, behavioural scientists have shed light on the unique relationship between dogs and humans and discovered that dogs have evolved to exhibit socio-cognitive abilities that are not found in other species 3 , including their closest living relatives, the wolves, as a new study by Salomons et al 4 , reported in this issue of Current Biology, confirms. Dogs' ability to read communicative human gestures such as pointing and their general motivation to engage with humans develop early and indeed a second new study reported in this issue of Current Biology by Bray et al 5 suggests that dogs are born to be 'human whisperers'.…”
mentioning
confidence: 99%
“…So, there were two central questions in the past decades: does a heritable component to dogs' communicative skills exist and are those skills unique to dogs? Bray et al 5 elegantly addressed the first of those two questions by studying the social cognitive skills of 375 eight-weekold retriever puppies bred to be assistance dogs. They presented the puppies with a series of tasks that systematically explored how skilful they are with human communication and how motivated they are to establish communicative interactions with people.…”
mentioning
confidence: 99%
See 1 more Smart Citation